Standardization of Seeds of Dolichos Biflorus Linn. - Gupta, S.K.; Sharma, P.K.; Ansari, S.H. (Asian Journal of Chemistry, 2016)
Seeds of Dolichos biflorus Linn. are considered to be very useful for removing kidney stones. These are used as astringent, diuretic and tonic. Seeds have been identified by their macroscopic and microscopic characters, cell contents, behaviour of powdered drug with different reagents and preliminary phytochemical analysis.